2022
DOI: 10.3389/fpsyg.2022.951149
|View full text |Cite
|
Sign up to set email alerts
|

Work–family and family–work conflict and stress in times of COVID-19

Abstract: This study aims to investigate the spillover impact of work-family/family–work conflict and stress on five major industrial sectors (education, textile, hospitals, banks, and retail stores), during the first wave of Covid-19. The purpose of this cross-sectional study is twofold; firstly, to test a hypothesized model where work-family/family-work conflicts are related to stress and where stress could exert a mediating role in such relationships. Secondly, we seek to explore the presence of these conflicts and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 83 publications
(117 reference statements)
1
13
1
1
Order By: Relevance
“…Although workers believe that their workload increased during the pandemic, they did not see an increase in labour conflict, nor did they seem willing to accept the risk of infection as part of their job. Both variables are not consistent in predicting PD, contrary to what has been observed in other studies, where an association was found between an increase in workload and PD [ 55 ], as well as in the association between labour conflict and PD [ 13 ]. This can be explained by their expected interaction with other variables.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Although workers believe that their workload increased during the pandemic, they did not see an increase in labour conflict, nor did they seem willing to accept the risk of infection as part of their job. Both variables are not consistent in predicting PD, contrary to what has been observed in other studies, where an association was found between an increase in workload and PD [ 55 ], as well as in the association between labour conflict and PD [ 13 ]. This can be explained by their expected interaction with other variables.…”
Section: Discussioncontrasting
confidence: 87%
“…However, after the pandemic, recent research suggests that job demands can affect work engagement and job burnout through job insecurity [ 12 ]. This is evidenced by the workload and risk of contagion from COVID-19 in health care workers, the economic and accommodation uncertainty in the hospitality sector, and the increased work-to-family conflicts for those forced to work from home, among others [ 10 , 13 ]. Consequently, the psychological distress associated to job demands, changes in the working conditions, insecurity, and lack of coping resources during the COVID-19 pandemic could lead to more serious impairments such as psychosomatic complaints and depression [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common goodness “with a higher purpose for our society and planet” is the logic behind the sustainability ( Contreras and Abid, 2022 ), which is formulated within the sustainable developmental goals (SDG) of United Nations ( United Nations, 2015 ). Coping with the grand challenges of the 21st century ( Aust et al, 2020 ; Elahi et al, 2022 ), like global climate change, pandemics and inequality of wealth, sustainable strategies and leadership ( Hallinger and Suriyankietkaew, 2018 ) are currently required for leading every organization to achieve sustainable performance ( Iqbal et al, 2020a ; Javed et al, 2021 ). For example, the heat waves that impact the world because of the temperature increase are affecting mainly those densely populated regions already-hot places ( Xu et al, 2020 ) forecast the critical need to have a healthcare infrastructure to attend to their necessities ( Bavel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The feeling of job burnout is known to have a negative impact on mental health (39), which may be mitigated by psychological resilience at the same time (37). Moreover, in the COVID-19 pandemic, the misty boundary between work and personal life potentially resulted in conflicts between work and family or family and work due to changes in the workplace, home environment, and social relationships (40). For healthcare workers, the stress of work-family balance could have a detrimental effect on their performance at work, reduce their feelings of wellbeing, and even cause more serious mental illness (41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%